Sex-related differences in self-paced all out high-intensity intermittent cycling: Mechanical and physiological responses - Panissa, Valéria Leme Gonçalves; Julio, Ursula F.; França, Vanessa [UNESP]; Lira, Fabio S. [UNESP]; Hofmann, Peter; Takito, Monica Y.; Franchini, Emerson (My University, 2016)
The purpose of this study was to compare sex-related responses to a self-paced all out high-intensity intermittent exercise (HIIE). 9 women and 10 men were submitted to a maximal incremental test (to determine maximum aerobic power - MAP and VO2peak), and an HIIE cycling (60x8s:12s, effort:pause). During the protocol the mean value of V̇ O2 and heart rate for the entire exercise (VO2total and HRtotal) as well as the values only in the effort or pause (V̇O2effort, VO2pause and HReffort and HRpause) relative to VO2peak were measured. Anaerobic power reserve (APR), blood lactate [La] and the respiratory exchange ratio (RER) were also measured. These variables were compared between men and women using the unpaired t test. Men used greater APR (109 ± 12%MAP vs 92 ± 6%MAP) with similar VO2total (74 ± 7 vs 78 ± 8% VO2peak), however, when effort and pause were analysed separately, V̇O2effort (80 ± 9 vs 80 ± 5%VO2peak) was similar between sexes, while V̇O2pause was lower in men (69 ± 6% vs 77 ± 11% VO2peak, respectively). Women presented lower power decrement (30 ± 11 vs 11 ± 3%), RER (1.04 ± 0.03 vs 1.00 ± 0.02) and [La]peak (8.6 ± 0.9 vs 5.9 ± 2.3 mmol.L-1). Thus, we can conclude that men self-paced HIIE at higher APR but with the same cardiovascular/aerobic solicitation as women.
Keywords: Anaerobic power reserve; Oxygen uptake; Sexual dimorphism